Developed mathematical model of solar thermal parabolic trough power plant at universiti teknologi petronas - Mohammad, S.T. (Asian Research Publishing Network, 2016)
This paper presents the conceptual design of a concentrating solar power plant (CSPP) using Direct Steam Generation method (DSG) in a parabolic trough solar field located in Universiti Teknologi Petronas, Perak, Malaysia. The conceptual design of the CSPP includes selection and sizing of solar field, power generation cycle, types of working fluids, sizing of the power block, etc.The conceptual design is based on a mathematical modeling of the CSPP. In the present solar thermal system, a turbine is integrated with 1.2 kW generators, and steam is produced by flow loop energized by solar parabolic trough concentrators. One of the most significant factors for the successful conceptual design of a CSPP is a precise determination of the transient solar radiation over the day and the season. Accordingly, in-situ measurements of the direct normal irradiance (DNI) has been carried out and used as input to the mathematical model. As a result of daily and seasonal variation of solar radiation, the developed model is designed in order to evaluate the transient behavior of the system and expected power production. Â©2006-2016 Asian Research Publishing Network (ARPN).